Respuesta :
Answer:
(-2, 3).
Step-by-step explanation:
x + 3y = 7
2x + 4y = 8
1 . x = 7 - 3y.
2. 2(7 - 3y) + 4y = 8
3. 14 - 6y + 4y = 8
-2y = -6
y = 3
4. Substitute y in the second equation:
2x + 4(3) = 8
2x = -14
x = -2..
The solution to the system of equations is: (-2, 3).
Solution to a System of Equations
Given the system of equations:
x + 3y = 7 --> eqn. 1
2x + 4y = 8 --> eqn. 2
First, isolate x in equation 1:
x = 7 - 3y
Plug in the value of x into eqn. 2 to solve for y.
2(7 - 3y) + 4y = 8
14 - 6y + 4y = 8
14 - 2y = 8
14 - 8 = 2y
6 = 2y
3 = y
y = 3
Find the value of x by substituting y = 3 into eqn. 1.
x + 3(3) = 7
x + 9 = 7
x = 7 - 9
x = -2
Therefore, the solution to the system of equations is: (-2, 3).
Learn more abut system of equations on:
https://brainly.com/question/13729904